Poczucie koherencji i akceptacja choroby a nasilenie dolegliwości bólowych u osób z chorobą dyskową odcinka lędźwiowego kręgosłupa = Sense of coherence, acceptance of an illness and pain intensity in patients with lumbar disc herniations - Kocjan, Janusz (Journal of Education, Health and Sport, 2016)
Kocjan Janusz. Poczucie koherencji i akceptacja choroby a nasilenie dolegliwości bólowych u osób z chorobą dyskową odcinka lędźwiowego kręgosłupa = Sense of coherence, acceptance of an illness and pain intensity in patients with lumbar disc herniations. Journal of Education, Health and Sport. 2016;6(4):481-492. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50702 http://ojs.ukw.edu.pl/index.php/johs/article/view/3498 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 28.04.2016. POCZUCIE KOHERENCJI I AKCEPTACJA CHOROBY A NASILENIE DOLEGLIWOŚCI BÓLOWYCH U OSÓB Z CHOROBĄ DYSKOWĄ ODCINKA LĘDŹWIOWEGO KRĘGOSŁUPA Sense of coherence, acceptance of an illness and pain intensity in patients with lumbar disc herniations Janusz Kocjan Studium Doktoranckie Wydziału Lekarskiego w Katowicach Śląski Uniwersytet Medyczny w Katowicach mgr Janusz Kocjan, Śląski Uniwersytet Medyczny w Katowicach, Studium Doktoranckie Wydziału Lekarskiego w Katowicach Streszczenie Wprowadzenie: Zespoły bólowe kręgosłupa (zbk) stanowią jedną z najbardziej rozpowszechnionych dolegliwości na całym świecie. Dane literaturowe wskazują, że czynniki psychospołeczne mają istotny wpływ na przewlekłe utrzymywanie się dolegliwości bólowych. Cel: Celem pracy było określenie związku pomiędzy poczuciem koherencji i stopniem akceptacji choroby a nasileniem dolegliwości bólowych dolnego odcinka kręgosłupa. Materiał i metody: Badania przeprowadzono wśród 93 pacjentów (43 kobiety i 50 mężczyzn) z rozpoznaniem choroby dyskowej odcinka lędźwiowo-krzyżowego kręgosłupa. Poczucie koherencji oceniono za pomocą kwestionariusza SOC-29, poziom akceptacji choroby - skalą AIS, nasilenie bólu - skalą VAS, a stopień niepełnosprawności spowodowanej bólem kręgosłupa – kwestionariuszem ODI. Wyniki: Średnie wartości punktowe wraz z odchyleniem standardowym dla poszczególnych kwestionariuszy prezentowały się następująco: SOC-29: 135,54 ± 25,61; AIS: 30,87 ± 6,96; VAS: 6,35 ± 3,16; ODI: 29,59 ± 16,99. U większości badanych stwierdzono mierny (37,63%) i poważny (41,93) stopień niesprawności kręgosłupa. Brak akceptacji choroby odnotowano u 11,82% badanych. Analiza zależności wykazała istotne statystycznie korelacje między poczuciem koherencji i stopniem akceptacji choroby a nasileniem dolegliwości bólowych w skali VAS oraz stopniem niepełnosprawności funkcjonalnej w skali ODI. Wnioski: Badani o wyższym poczuciu koherencji oraz wysokim stopniu akceptacji choroby odczuwają mniejsze nasilenie dolegliwości bólowych oraz charakteryzują się mniejszym stopniem niepełnosprawności funkcjonalnej w porównaniu do osób z niskim poczuciem globalnej orientacji życiowej oraz niskim stopniem akceptacji choroby. Słowa kluczowe: poczucie koherencji, akceptacja choroby, ból kręgosłupa, SOC-29, choroba dyskowa. Summary Introduction: Back pains are one of the most prevalent diseases worldwide. Literature data indicate, that psychosocial factors have an significant influence on the persistence of pain. Aim: The aim of the study was to determine the relationship between sense of coherence and degree of acceptance of an illness with the intensity of low back pain. Material and methods: The study was conducted among 93 patients (43 women and 50 men) diagnosed with lumbosacral spine discopathy. The sense of coherence was evaluated using the SOC-29 questionnaire, illness acceptance degree - using AIS scale, pain intensity by means of VAS scale, while the perceived level of disability associated with low back pain was evaluated with the ODI Scale. Results: Mean values obtained from questionnaires were as follows: SOC-29: 135,54 ± 25,61; AIS: 30,87 ± 6,96; VAS: 6,35 ± 3,16; ODI: 29,59 ± 16,99. In case of the majority of respondents, mediocre (37,63%) and serious (41,93%) degree of spine disability was found. Lack of acceptance of an illness was observed in 11.82% of patients. Significant dependencies between sense of coherence, illness acceptance with intensity of feeling of pain and degree of disability were found. Conclusions: Subjects with a high sense of coherence and with a high degree of illness acceptance experience lower pain intensity and are characterized by a lower degree of functional disability compared to subjects with low self global life orientation and a low degree of acceptance of the disease. Key words: sense of coherence, illness acceptance, back pain, SOC-29, disc hernia.